Hikers’ pro-environmental behavior in national park: Integrating theory of planned behavior and norm activation theory - Huazhen Sun; Huazhen Sun; Qing Zhang; Qing Zhang; Weifeng Guo; Kaimiao Lin (Frontiers in Forests and Global Change, 2022)
Hikers’ intention for pro-environmental behavior (PEB) directly affects the sustainable development of protected areas, but few studies have been conducted from the perspective of theoretical integration. This study explores the intention of hikers’ PEB from the perspective of individual hikers, based on the theory of planned behavior and norm activation theory. Researchers surveyed 456 hikers in Wuyishan National Park, and the data analysis method employed was structural equation modeling. The results demonstrate that the model integrating TPB and NAM was accepted of hikers’ PEB in national park, and for the hiker, internal demand was found to precede external stimulus for their behavior. The study sheds light on how to better comprehend and advocate for PEB in national parks.